Pengelolaan Sampah Bernilai Ekonomi Berbasis Masyarakat - Zairinayati, Zairinayati; Maftukhah, Nur Afni; Novianty, Novianty (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
Waste can cause environment problem in many aspects if it is not handled properly. On the other hand, waste can give safe and comfort feelings if it is well managed. Besides, the right waste management can be a product that has economic and social values. It can be done through social empowerment program. The program is aimed at changing the perspective and knowledge of the people about waste, so that waste can be managed properly and has economic value. Meanwhile, the program target is the people in Sungsang Village, Banyuasin, Sumatera Selatan. The program is carried out in various ways, namely socialization, training, practice, processing accompaniment, and waste management. The result of the empowerment conducted showed that there was a change in the perspective, knowledge, and social behaviour towards waste. The interest of the people to manage waste independently has grown well. They got the feeling of safe and comfort, and the economic benefit with proper and wise waste management, both the inorganic and organic waste. The program is hoped to be sustainable so that waste problems can be minimized disseminated to the people in Sungsang Village, Banyuasin, Sumatera Selatan.